The Effect of AI-Based Deep Learning on Narrative Writing Skills for Elementary School Students - Eka Sopiya Khoirul Muna; Nur Khotimah; Thoif Pujiwati; Atrianing Yessi Wijayanti (Proceeding of the International Conference on Global Education and Learning, 2025)
Narrative writing skills are crucial for the literacy development of elementary school students. However, many students face challenges in writing narrative essays due to limited vocabulary, grammar understanding, and imagination. Traditional teaching methods often fail to address these issues. This study explores the impact of AI-based Deep Learning on narrative writing skills. Using a quantitative approach with an experimental design, the research employed a pretest-posttest design with a nonrandomized control group. The study involved 65 students from SD 4 Sidomulyo, including 30 students from class IV A and 35 from class IV B. A nonprobability sampling technique with saturated sampling was used. Data was collected through tests, and content validity was applied for validation. Hypothesis testing with the Independent Samples t-test yielded a significance value of 0.001 (p < 0.05) and a calculated t-value of 3.472, which is greater than the t-table value of 2.0024. These results indicate that AI-based Deep Learning significantly affects narrative writing skills in elementary school students. Keywords: AI-Based Deep Learning, Narrative Writing Skills.